POTENSI ALAT MUSIK BATAK TOBA SEBAGAI SUMBER BELAJAR MATEMATIKA DALAM MENGEMBANGKAN KEMAMPUAN KOMUNIKASI MATEMATIS - Hadi Harianto (MEGA: Jurnal Pendidikan Matematika, 2022)
This study aims to explore the potential of ethnomatematics in Simalungun and the potential for integration of ethnomatematics in learning. This research is a survey research. The study was conducted in Simalungun with the selection of objects carried out by purposive sampling. The collection methods used in this study are observation, documentation, and literature study. After the data is collected then it is analyzed qualitatively. The study results were also conducted to find out the potential integration of ethnomatematics in learning to improve students' mathematical communication skills. The results of research that have been carried out, the musical instruments Sarune Bolon, Hasapi, and Taganning are closely related to the concept of mathematical flat figure. Ethnomatematics has the potential to improve students' mathematical communication skills, if integrated with appropriate learning materials and models.